درهم نادر للسيدة أم الأمين ضرب البستان سنة (186هـ/ 802) - نايف بن عبدالله الشرعان (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2024)
تتناول هذه الدراسة درهمًا عباسيًا تذكاريًا نادرًا للغاية، محفوظًا في مجموعة الأستاذ حسين إبراهيم القراشي، يحمل كنية السيدة زبيدة (أم الأمين)، جرى سكه في البستان سنة (186ه/ 802م)، على طراز الدراهم العباسية المعاصرة له، تخليداً لمناسبة إتمام مشاريع مرحلة مهمة من مراحل مشروعها العظيم طريق الحج العراقي، أو ما يعرف بدرب زبيدة، واحتفاءً بمناسبة إتمام بيعة ابنها محمد الأمين بولاية العهد بشكل نهائي، أثناء حج الخليفة هارون الرشيد خلال تلك السنة، حمل هذا الدرهم عدد من النصوص الكتابية التي تظهر لأول مرة على النقود الإسلامية، وتم تناول هذا الدرهم بالدراسة الوصفية والتحليلية، وتبيان دلالة عباراته الدينية، والسياسية، والاجتماعية في ضوء المعلومات التاريخية المعاصرة له. Abstract This research presents an extremely rare commemorative Abbasid Dirham under the name of Zubaida (Um Al-Amin). The Dirham is from the collection of Mr. Hussain Ibrahim Al-Qarashi from Kuwait. The Dirham was minted in Albustan in (186 AH/ 802 AD), holding the Abbasid style to celebrate the completion of the first phase of an important milestone "The Iraqi Pilgrimage Route or Zubaida Route" in addition, to celebrate the completion of the pledge of allegiance to her son Alamin during the pilgrimage of Caliph Harun Alrashid that year. This coin has several texts that appeared for the first time on Islamic coins. In this research, light is shed on the Dirham through analyzing political, social, and religious meanings and events linked to that historical time.